Slope Failure Assessment In Penang Island Using Geoelectrical Methods - Azman, Muhamad Iqbal Mubarak Faharul (2018)
Slope failures never cease to end in hilly and slope area every year. This is very dangerous especially for those who lives within the proximity. However, slope is not only found in residential area but also alongside highways and federal roads. This research aims to investigate slope at the selected highly suspected area in Penang Island (Sungai Batu, Bukit Relau and Air Hitam) using 2D resistivity and induced polarization methods and to analyse and correlate the results from 2D resistivity method, induced polarization method, laboratory tests and rainfall distribution for slope failure potentials. The study areas were selected based on the previous studies and cases of slope failure reported in Penang Island. Based on the results.